(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This work aims to propose a reflection on curation in the performing arts and the role of the curator in his/her professional practice in contemporary times, considering artistic actions in the Brazilian context. A historical path is presented, covering a trajectory in the context of modern arts, when the profession is established with the current characteristics. Then, critical perspectives on the role of the curator are elaborated, analyzing the attributions necessary for the creation of a program in performing arts. Finally, the curator is conceived as a manager of expectations, being responsible for proposing debates about society and art itself, based on the relationship established between artist, work and public within a performing arts programming.